Stress and Burnout amongst Business School Staff - Steyn, Renier (International Journal of Educational Studies, 2025)
This study aims to evaluate stress levels and burnout experiences among business school staff while identifying the primary workplace stressors contributing to burnout. It addresses the need for an updated assessment in the post-Covid-19 work environment, with the ultimate goal of informing the development of targeted interventions to mitigate burnout and improve overall staff wellbeing. This study employed a cross-sectional survey design targeting the complete business school staff population. Data were collected using a self-designed survey measuring workplace stressors alongside the Maslach Burnout Inventory – Educators Survey (MBI-ES). Analyses involved reliability tests (Cronbach’s alpha), Confirmatory Factor Analysis, one-sample t-tests, and correlation analyses using standard statistical software. The study achieved a 34% response rate with demographics representative of the business school staff. Results indicated moderate emotional exhaustion, low depersonalisation, and high personal accomplishment. Workplace stressors were observed at average levels and correlated most strongly with emotional exhaustion, with task overload and restricted autonomy emerging as the primary contributors to burnout. The findings can be applied in academic administration, human resource management, and organisational behaviour within higher education settings. The insights support the development of targeted interventions, policies, and wellbeing programmes to reduce burnout. Additionally, the study indicates that while theory links certain factors with others, these connections vary in strength when applied in practice. The study offers a contemporary perspective on stress and burnout in the context of the post-Covid-19 work environment. By integrating a self-designed survey with the established Maslach Burnout Inventory – Educators Survey, it advances current knowledge on burnout antecedents. The somewhat surprising results provide insights to inform targeted managerial interventions and enhance staff wellbeing strategies.